A Study on Anglo-Scandinavian bý(r)-names: Statistical Analysis and Case-Studies - Neal, Joshua (2023)
This thesis is a large-scale analysis of place-names in England and southern Scotland that contain the settlement-term Old Norse (ON) bý(r) as their generic element. This analysis is based on what is, to my knowledge, the largest corpus of Anglo-Scandinavian bý(r)-names ever constructed. It has allowed for large-scale analysis of their geographical, chronological, and linguistic contexts, and analyses of bý(r)-name sub-groups within these contexts.